Polymers - Inman , Roger; Jones , Loretta; University of Illinois (Illinois : Board of Trustees , University of Illinois, 1984)
About polymers , includes Synthesis and properties of polymers
part 1. Synthesis part 2. Properties of polymers
Producer , director , Roger Inman ; writer , Loretta Jones
Narrator : Loretta Jones , Steve Zundahl
Keywords: Polymers; Polymers -- Analysis; Polymerization; Chemistry , Technical